Investigation Of Different Harvesting Methods For Microalgae Coccomyxa Sp. Biomass - Khoo, Zenyang (Pusat Pengajian Teknologi Industri, 2020)
Microalgae harvesting methods can currently be classified as mechanical, chemical, biological and electrical. Centrifugation, flocculation and filtration are among the top three preferred harvesting techniques to obtain microalgal biomass for applications such as biofuel, human and animal food, and water quality restoration. The present study investigated the variables affecting the biomass recovery efficiency via centrifugation, flocculation and filtration method. Coccomyxa sp. microalgae strain was locally isolated and cultivated for the investigation and comparison of harvesting efficiency for each method. Based on the results in this study, a centrifugal speed of 5000 rpm can give rise to harvesting efficiency >95% at 5 minutes. Centrifugation time at 2 minutes and above was capable of attaining >90% of microalgal biomass recovery while centrifugation time longer than 5 minutes did not show significant increase in harvesting efficiency.